prevalance of Helicobacterpylori infection based on gastric biobsy and stool antigen test in adult patients with dyspepsia. - Hmad, Esmael; Daowd, Ali; Esmae, Alaa Emad (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: Helicobacter pylori infection is one of the most common human infections in the world. This infection is a major cause of chronic gastritis and peptic ulcer, and may be complicated by gastric cancer and gastric MALT lymphoma . There are several methods to diagnose H pylori infection including invasive,and noninvasive procedures.Invasive procedures using mucosa biopsies taken during endoscopy (mainly culture, histology,pcr, and the rapid urease test) are expensive and harmful to patients. Noninvasive procedures :mainly 13Cor 14C urea breath tests (UBTs), serological tests which include markers of exposure to H. pylori , and Hpylori stool antigen test is simple, fast ,relatively and inexpensive . Aim of the study: was to investigate the prevalence of H. pylori infection among patients with dyspepsia in our society, the sensitivity, specificity,and accuracy of Hpylori stool antigen test. Methods: 100 patients whith dyspepsia were evaluated by testing stool samples for H.pylori stool antigen ,and undergoing upper endoscopy and gastric biopsies. The biopsies were stained with Giemsa staining to determine Helicobacter pylori . Results: The prevalence of Helicobacter pylori infection among dyspeptic patients was 62% by gastic biopsy ,and 39% by stool antigen test.The prevalence of HP infection in patients with functional dyspepsia was 36% . Fecal test sensitivity, specificity, and accuracy were 57%,90%,69% respectively. Conclusion: The H.pyloi infection is common in dyspeptic patients. The sensitivity of fecal test in our study is low .So, we recommend not to use it in detection H pylori infection in our hosiptal. يعتبر الانتان بالملتوية البوابية من أشيع الانتانات التي تصيب الانسان, ويعتبر سببا مهما لالتهاب المعدة المزمن والداء القرحي وله علاقة بحدوث سرطان المعدة ولمفوما MALT . يوجد طرق متعددة لتشخيصه تتضمن طرق غازية وغير غازية . أما الطرق الغازية فتعتمد على اجراء تنظير هضمي علوي مع أخذ خزعات نسيجية وتحري وجود الملتوية البوابية عبر الفحص النسيجي أو الزرع أو اختبار اليورياز أو عبر تفاعل البوليميراز المتسلسل PCR ، وهي تعتبر طرق راضة للمريض وعالية الكلفة .وأما الطرق غير الغازية فتشمل اختبار النفس والفحوص المصلية واختبار المستضد البرازي والذي يعتبر فحص سريع وسهل الاجراء وقليل الكلفة. هدف البحث: معرفة انتشار الانتان بالملتوية البوابية لدى مرضى عسرة الهضم في مجتمعنا , وتحري حساسية ونوعية ودقة اختبار المستضد البرازي . طرائق البحث: تم جمع عينة براز من 100 مريض ممن يعانون من أعراض عسرة هضم وخضعو لاجراء تنظير هضمي علوي مع أخذ خزعات معدية ، حيث تم اجراء اختبار المستضد البرازي ، وتلوين الخزع بملون غيمزا لتحري وجود الملتوية البوابية . النتائج : بلغت نسبة انتشار الانتان بالملتوية البوابية لدى مرضى عسرة الهضم 62 % اعتمادا على الخزعة المعدية و39% بالاعتماد على اختبار المستضد البرازي . بلغت نسبة انتشار الانتان عند مرضى عسرة الهضم الوظيفية 36% . بلغت حساسية ونوعية ودقة اختبار المستضد البرازي 57%, 90% , 69% على الترتيب. الخلاصة : الانتان بالملتوية البوابية شائع عند مرضى عسر الهضم . حساسية اختبار المستضد البرازي كانت منخفضة في دراستنا وبالتالي لا نستطيع الاعتماد عليه لكشف الانتان بالملتوية البوابية.